2015
DOI: 10.25260/ea.15.25.1.0.58
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volcanic ash over Orthoptera survival in Patagonia

Abstract: The aim of this work was to evaluate the ash toxicity from the Puyehue-Cordón Caulle volcanic complex on the survival of two Orthopteran species: the grasshoper Dichroplus vittigerum and the green locust Brugilis sp. Two grain size were used to evaluate the effect of volcanic eruption on these insects. Chemical analyses from this eruption proved that the ashes were very abrasive and predominantly composed of silica shards (SiO 2 ) and aluminia (Al 2 O 3 ), two substances with insecticidal properties. In northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
3
0
2
Order By: Relevance
“…1a). This is common in invertebrate predators (Holling 1959a, Hassell et al 1977) and has also been reported for the same Chrysoperla species in this study, but feeding on other prey species (Holling 1959a, Atlihan et al 2004, Fernandez-Arhex and Corley 2004, Mushtaq and Khan 2010, Hassanpour 2011, Palomares-Pérez et al 2019). In all cases, the curves diverged at prey density greater than 32, and C. carnea had greatest consumption ability than the other two species studied, even at 256 M. sacchari nymphs.…”
Section: Resultssupporting
confidence: 86%
“…1a). This is common in invertebrate predators (Holling 1959a, Hassell et al 1977) and has also been reported for the same Chrysoperla species in this study, but feeding on other prey species (Holling 1959a, Atlihan et al 2004, Fernandez-Arhex and Corley 2004, Mushtaq and Khan 2010, Hassanpour 2011, Palomares-Pérez et al 2019). In all cases, the curves diverged at prey density greater than 32, and C. carnea had greatest consumption ability than the other two species studied, even at 256 M. sacchari nymphs.…”
Section: Resultssupporting
confidence: 86%
“…In particular, the Holling Type II functional response assumes that the predation rate is proportional to the encounter rate between prey and predators but also takes into account predator satiation as prey density increases. In other words, the Holling Type II functional response in a prey-predator model captures the following observed behavior in nature: predators cannot consume prey indefinitely at constant rates, but their efficiency decreases as prey density increases [22]. One mathematical expression of the Holling Type II functional response is as follows:…”
Section: Biological Backgroundmentioning
confidence: 99%
“…Traditionally, statistical analysis of the functional response experiments is carried out by selecting the functional response model by a logistic regression thereby reducing the problem of differentiating between a hyperbolic curve (type II functional response) and a sigmoid curve (type III functional response). The use of a non-linear regression in a frequentist framework is then recommended to estimate the parameters of the curve [51]. Since this approach is not appropriate for selecting several models that compete with one another, Johnson and Omland [52] proposed the use of the Bayesian system.…”
Section: Model Fitting and Selectionmentioning
confidence: 99%